(untitled) (Contemporary Journal of Social Science Review, 2026)
Dielectric constant measurement is an important topic in electronic circuit design. In this study, circular and square SRR-based sensors are proposed to overcome the limitations of conventional measurement methods. Both SRR-based sensors are loaded with a quarter-wavelength coplanar waveguide (CPW) transmission line with two ports and have a size of 35 mm x 35 mm x 1.27 mm. The transmission coefficient is used as the measurement parameter. S21 resonance shifts when the material under test (MUT) is put on top of the SRR. The proposed circular and square SRR sensors are fabricated on the Rogers RO3210 substrate material with a relative permittivity of 10.2. The resonance frequency of the circular SRR is 3.31 GHz, while the square SRR resonates at 2.67 GHz. A linear relationship is found between resonance shift and dielectric constant for both proposed sensors. A good coefficient of determination is obtained, and the linear equation is used to predict the dielectric constant of Rogers RT6002, FR4, and Rogers TMM10 for validation purposes. Experiment measurement proved that the proposed circular and square SRR sensors have high accuracy in dielectric constant measurement.